Pragmatic evolution : applications of evolutionary theory - Poiani, Aldo (Cambridge University Press, 2012)
"Of what use is evolutionary science to society? Can evolutionary thinking provide us with the tools to better understand and even make positive changes to the world? Addressing key questions about the development of evolutionary thinking, this book explores the interaction between evolutionary theory and its practical applications. Featuring contributions from leading specialists, Pragmatic Evolution highlights the diverse and interdisciplinary applications of evolutionary thinking: their potential and limitations. The fields covered range from palaeontology, genetics, ecology, agriculture, fisheries, medicine, neurobiology, psychology and animal behaviour; to information technology, education, anthropology and philosophy. Detailed examples of useful and current evolutionary applications are provided throughout. An ideal source of information to promote a better understanding of contemporary evolutionary science and its applications, this book also encourages the continued development of new opportunities for constructive evolutionary applications across a range of fields"--